Controlling currency mismatches in emerging economies - Goldstein, Morris, 1944-; Turner, Philip (Washington, DC : Institute for International Economics, 2004)
A summary of what we know about the origins of currency mismatching in emerging economies. It discusses how best to define and measure currency mismatching and reviews policy options for reducing the size of the problem.
Includes bibliographical references (p. 145-152) and index.
oif 01/09/15
Loan
Keywords: Foreign exchange rates -- Developing countries; Foreign exchange administration -- Developing countries; Monetary policy -- Developing countries